Declines in HIV incidence among men and women in a South African population-based cohort - Vandormael, Alain; Akullian, Adam; Siedner, Mark; Oliveira, Tulio de; Bärnighausen, Till; Tanser, Frank (Nature Communications, 2019)
Here, the authors investigate the outcome of prevention services scale-up on HIV incidence in a South African large population-based HIV surveillance cohort with over a decade of follow-up and associate a 43% reduction in incidence to earlier male medical circumcision and increased levels of antiretroviral therapy coverage.
Gesehen am 22.01.2020